'I'll Make It Up to You:' Examining the effect of apologies on forgiveness. Issue 6 (2nd November 2018) - Jeter, Whitney K.; Brannon, Laura A.
Abstract: Receiving an apology is a key component to the management of conflict and the likelihood that forgiveness will occur. However, not all apologies are effective at alleviating interpersonal conflict. The current research focused on the content of an apology (e.g. 'I'll make it up to you; I was wrong; I feel bad that I did this …') and the differential impact this content may have on self-reported and behavioral forgiveness among young adults. Seven different apologies were designed and tested for effectiveness within an experimentally created transgression. Undergraduate students ( N = 199) completed a distribution of resources task in which the researchers simulated a transgression experience without the students' knowledge. Following the transgression, students received one of the seven apologies. Results indicate that receiving an apology that expressed a desire to compensate for wrongdoing appeared to be the most effective apology in terms of promoting both self-reported and behavioral forgiveness.